PENERAPAN STRATEGI PEMBELAJARAN AKTIF GROUP TO GROUP EXCHANGE (GGE) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA POKOK BAHASAN KESETIMBANGAN KIMIA DI KELAS XI IPA SMA NEGERI 11 PEKANBARU - Nasution, Dessy Amalina; Copriady, Jimmi; Herdini, Herdini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Research on active learning strategy group to group exchange (GGE) has been implemented in SMAN 11 Pekanbaru. The research aimed to know the increase student’s achievement learning and the influence of GGE strategy on students achievement learning on the subject of Chemical Equilibrium in XI IPA SMAN 1 Pekanbaru. The type of research is experimental research with pretest-posttest design . XI IPA SMAN 11 Pekanbaru consisting of 3 classes performed normality and homgeneity test using prerequisite data so that obtained 2 randomly selected samples that is student in class XI IPA 2 as an experimental class and students in class XI IPA 3 as a control class. The experimental class is the class that applied GGE active learning strategy while the control class is not applied GGE active learning strategy.This research instrument is a quastion of chemical equilibrium that has been tested validation and reliability and obtained valid and reliable data as research instrument. The hypothesis testing using U Mann-Whitney test obtained z arithmetic > z table is 3.89> 1, 64, based on hypothesis testing concluded that the implementation of GGE active learning strategy can increase student achievement learning on the subject of chemical equilibrium in class XI IPA SMAN 11 Pekanbaru . The influence of GGE's active learning strategy on student achievement learning is 34.3%.Keywords : Chemical Equilibrium,Students Achievement, Group to Group Exchange (GGE)